Potential of TPS 3R as Part of The Development of Taro Tourist Village, Tegallalang District, Gianyar District - I Gusti Ketut Indra Pranata Darma; I Ketut Arta Widana; I Putu Suyasa Ariputra (Media Wisata, 2023)
The shift in the tourism industry from mass tourism to alternative tourism has led to various interesting developments. One of these developments is related to the existence of tourist villages as a form of alternative tourism. Tourist trends have also changed with their interest in the existence of local communities in presenting their various original attractions. Local communities offer a variety of new experiences in a tourist village to tourists with various purposes. One of the villages that offers local community involvement is Taro Village, Tegallalang Subdistrict, Gianyar Regency with TPS (Temporary Disposal Site) 3R (Reduce-Reuse-Recycle) which is one of the components of tourism village development. This research uses descriptive qualitative methods. In-depth interviews were conducted with the managers of Bumdes and TPS 3R, the local community which is adjacent to the TPS residents during the researcher's observation. The results of this study indicate that in destination development, the availability of packages (Available Package) is one component that still needs to be developed in both tourist villages. TPS 3R has involved the Community as an important part of the development of taro tourism village.  The role of the Bumdes unit is an integrated and important part of the basic requirements for the development of tourism. The impact that arises because of the TPS 3R can be seen in the socio-economic side that mobilizes both directly and indirectly the unit and the community around the TPS. Socio-cultural and environmental impacts that arise such as the transfer of experience to visitors in educating waste sorting to the importance of caring for the environment with the existence of TPS 3R.